2023
DOI: 10.1186/s13041-023-00999-y
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of neuroligin4, an autism-related postsynaptic molecule, in the human brain

Abstract: NLGN4X was identified as a single causative gene of rare familial nonsyndromic autism for the first time. It encodes the postsynaptic membrane protein Neuroligin4 (NLGN4), the functions and roles of which, however, are not fully understood due to the lack of a closely homologous gene in rodents. It has been confirmed only recently that human NLGN4 is abundantly expressed in the cerebral cortex and is localized mainly to excitatory synapses. However, the detailed histological distribution of NLGN4, which may ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…One study found that mice prenatally exposed to valproic acid (VPA) exhibited cognitive and motor deficits in Y-maze learning, which may be due to reduced levels of proteins involved in excitatory synapse formation, such as Nlgn1 and PSD-95 ( 80 ). Among the subtypes of Nlgn, the Nlgn2 gene is often reduced in expression in severe neuropsychiatric disorders ( 81 ), Nlgn3 primarily mediates enteric neuron-neuroglial ( 82 ), and Nlgn4 is primarily involved in functioning in intelligence, social skills, sleep, and arousal ( 83 ) and impairments of all of these subtypes are associated with ASD. Additionally, GPR85, an ASD risk factor, associates with NLGN-associated postsynaptic density protein PSD-95 in brain, interfering with dendritic formation via the NLGN-PSD-95 receptor complex and causing neural excitation-inhibition imbalance, affecting learning and memory ( 84 ).…”
Section: Neural Pathwaysmentioning
confidence: 99%
“…One study found that mice prenatally exposed to valproic acid (VPA) exhibited cognitive and motor deficits in Y-maze learning, which may be due to reduced levels of proteins involved in excitatory synapse formation, such as Nlgn1 and PSD-95 ( 80 ). Among the subtypes of Nlgn, the Nlgn2 gene is often reduced in expression in severe neuropsychiatric disorders ( 81 ), Nlgn3 primarily mediates enteric neuron-neuroglial ( 82 ), and Nlgn4 is primarily involved in functioning in intelligence, social skills, sleep, and arousal ( 83 ) and impairments of all of these subtypes are associated with ASD. Additionally, GPR85, an ASD risk factor, associates with NLGN-associated postsynaptic density protein PSD-95 in brain, interfering with dendritic formation via the NLGN-PSD-95 receptor complex and causing neural excitation-inhibition imbalance, affecting learning and memory ( 84 ).…”
Section: Neural Pathwaysmentioning
confidence: 99%
“…Given that many XLID genes are neuronally enriched (4)(5)(6)(7)(8)(9)(10), an a priori hypothesis is that ZDHHC9 acts in neurons. However, patients with ZDHHC9 mutations have grossly normal gray matter (GM) but reduced brain white matter (WM) volume, especially in the corpus callosum (CC)…”
Section: Introductionmentioning
confidence: 99%